2018
DOI: 10.1016/j.heliyon.2018.e00620
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in amino acid metabolism during growth by Staphylococcus aureus following exposure to H2O2 – A multifactorial approach

Abstract: Temperature and pH are known to vary in a wound site due to the immune response and subsequent healing processes. This study used a multifactorial design to examine the cellular responses of Staphylococcus aureus to hydrogen peroxide (0–100 mM) when bacteria were grown in temperatures of 37 ± 2 °C and pH 7 ± 1, conditions potentially encountered in wound sites. A centroid sample was included in the design which represented the mid-point values of all three environmental parameters (37 °C, pH 7, 50 mM H2O2). Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Another study showed that limited proline in the media impaired staphylococcal growth and survival (Schwan et al, 2004). likewise, combinations of subtle environmental parameters led to substantial modifications in amino acid uptake profiles associated with significant patterns of cytoplasmic amino acids (Murphy et al, 2018). Similarly, significant changes in cytoplasmic amino acid compositions of S. aureus in response to variation in pH, temperature and osmotic pressure were observed (Alreshidi et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Another study showed that limited proline in the media impaired staphylococcal growth and survival (Schwan et al, 2004). likewise, combinations of subtle environmental parameters led to substantial modifications in amino acid uptake profiles associated with significant patterns of cytoplasmic amino acids (Murphy et al, 2018). Similarly, significant changes in cytoplasmic amino acid compositions of S. aureus in response to variation in pH, temperature and osmotic pressure were observed (Alreshidi et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Another study determined significant changes in the fatty acid composition and cell sizes of Staphylococcus lugdunensis in response to alterations in environmental conditions including changes in pH and temperature 8 . A recent study exhibited that hydrogen peroxide combined with other environmental factors such as altered pH and temperature led to very different metabolic profiles of a clinical isolate of S. aureus 10 , suggested these alterations in amino acids were essential for survival under changes in the environmental conditions. Moreover, a new study revealed that S. aureus taken up and released different levels of amino acids following growth in altered environmental conditions 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was assumed that characteristic and specific changes in the amino acid and fatty acid metabolites as well as protein composition led to the survival of S. aureus when exposed to confined nutrition in combination with higher concentrations of NaCl 9 . A recent study indicated that hydrogen peroxide (H 2 O 2 ) combined with various temperatures and pH induced alterations in the amino acid profiles of clinical isolate of S. aureus 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This was shown by an analysis of the amino-acid profile of S. aureus after exposure to hydrogen peroxide [64]. Modifications to the amino-acid profile influence many biological pathways in cells, as amino acids are required for protein synthesis, and used for synthesis of the cell-wall and nucleic acids, and they can be used as energy substrates [64]. Reductions in cytoplasmic amino acids has been associated with slower rates of metabolism, to conserve energy for basal metabolism [65].…”
Section: Response Mechanisms To Ddac Of the Ddac-tolerant S Epidermimentioning
confidence: 93%
“…Modifications to amino acids have been shown to be a response mechanism for a changing environment. This was shown by an analysis of the amino-acid profile of S. aureus after exposure to hydrogen peroxide [64]. Modifications to the amino-acid profile influence many biological pathways in cells, as amino acids are required for protein synthesis, and used for synthesis of the cell-wall and nucleic acids, and they can be used as energy substrates [64].…”
Section: Response Mechanisms To Ddac Of the Ddac-tolerant S Epidermimentioning
confidence: 99%